2016
DOI: 10.1164/rccm.201602-0353oc
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-like Features and Clinical Course of Chronic Obstructive Pulmonary Disease. An Analysis from the Hokkaido COPD Cohort Study

Abstract: The presence of asthma-like features was associated with better clinical course in patients with COPD receiving appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 32 publications
12
108
4
Order By: Relevance
“…Similar results were found in a study of 137 patients with COPD hospitalized in Italy . Studying the effect of asthma‐like features on the clinical course of COPD in Japan, Suzuki et al also found that blood eosinophils <300 cells/μL was associated with a significantly faster decline in post‐bronchodilator FEV1 . With regard to pulmonary infections, it has been suggested that in COPD, a low eosinophil count correlated with more frequent bacterial infections and a higher bacterial load of Haemophilus influenzae , Moraxella catarrhalis and Streptococcus pneumoniae .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were found in a study of 137 patients with COPD hospitalized in Italy . Studying the effect of asthma‐like features on the clinical course of COPD in Japan, Suzuki et al also found that blood eosinophils <300 cells/μL was associated with a significantly faster decline in post‐bronchodilator FEV1 . With regard to pulmonary infections, it has been suggested that in COPD, a low eosinophil count correlated with more frequent bacterial infections and a higher bacterial load of Haemophilus influenzae , Moraxella catarrhalis and Streptococcus pneumoniae .…”
Section: Discussionsupporting
confidence: 65%
“…17 Studying the effect of asthma-like features on the clinical course of COPD in Japan, Suzuki et al also found that blood eosinophils <300 cells/lL was associated with a significantly faster decline in post-bronchodilator FEV1. 35 With regard to pulmonary infections, it has been suggested that in COPD, a low eosinophil count correlated with more frequent bacterial infections and a higher bacterial load of Haemophilus influenzae, Moraxella catarrhalis and Streptococcus pneumoniae. Furthermore, there are several reports that high blood eosinophil count in COPD is associated with better response to corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have consistently found that the BMI of Asian patients is lower than that of Western patients. [25][26][27][28] Adverse effects of COPD drugs can occur because of differences in BMI.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…The influence of ACOS defining criteria on prognosis was highlighted by Suzuki et al who investigated how asthma-like features influenced the clinical course of patients with COPD after excluding those with physician diagnosed asthma (21). Within this 10-year Japanese multicentre observational study, neither bronchodilator reversibility, blood eosinophilia or atopy were associated with worse clinical outcome.…”
Section: Asthma-copd Overlapmentioning
confidence: 99%